Early versus delayed antiretroviral therapy based on genotypic resistance test: Results from a large retrospective cohort study. Issue 8 (9th April 2022) - Bavaro, Davide F.; De Vito, Andrea; Pasculli, Giuseppe; Bouba, Yagai; Magnasco, Laura; Pincino, Rachele; Saladini, Francesco; Lattanzio, Rossana; Corsini, Romina; Arima, Serena; Zazzi, Maurizio; Incardona, Francesca; et al.
Abstract: Rapid start of antiretroviral therapy (ART) pending genotypic resistance test (GRT) has been recently proposed, but the effectiveness of this strategy is still debated. The rate of virological success (VS), defined as HIV‐RNA < 50 copies/ml, with and without GRT was compared in drug‐naïve individuals enrolled in the Italian ARCA cohort who started ART between 2015 and 2018. 521 individuals started ART: 397 without GRT (pre‐GRT group) and 124 following GRT (post‐GRT group). Overall, 398 (76%) were males and 30 (6%) were diagnosed with AIDS. In the pre‐GRT group, baseline CD4+ cell counts were lower ( p  < 0.001), and viral load was higher ( p  < 0.001) than in the post‐GRT group. The estimated probability of VS in pre‐GRT versus post‐GRT group was 72.54% (CI95 : 67.78–76.60) versus 66.94% (CI95 : 57.53–74.26) at Week 24 and 92.40% (CI95 : 89.26–94.62) versus 92.92% (CI95 : 86.35–96.33) at Week 48, respectively ( p  = 0.434). At Week 48, VS was less frequent among individuals with baseline CD4+ cell counts <200 versus >500 (90.33% vs. 97.33%), log viral load <5.00 versus >5.70 log10 cps/ml (97.17% vs 78.16%;  p  < 0.001), and those treated with protease inhibitors or non‐nucleoside reverse transcriptase inhibitors versus those treated with integrase strand transfer inhibitors ( p  < 0.001). The rate of VS does not seem to be affected by an early ART initiation pending GRT results, but it could be influenced by the composition of the ART regimen, as well as immuno‐virological parameters.